Single-crystalline YIG flakes with uniaxial in-plane anisotropy and diverse crystallographic orientations - R. Hartmann; Seema; I. Soldatov; M. Lammel; D. Lignon; X. Y. Ai; G. Kiliani; R. Schäfer; A. Erb; R. Gross; J. Boneberg; M. Müller; et al. (APL Materials, 2024)
We study sub-micron Y3Fe5O12 (YIG) flakes that we produce via mechanical cleaving and exfoliation of YIG single crystals. By characterizing their structural and magnetic properties, we find that these YIG flakes have surfaces oriented along unusual crystallographic axes and uniaxial in-plane magnetic anisotropy due to their shape, both of which are not commonly available in YIG thin films. These physical properties, combined with the possibility of picking up the YIG flakes and stacking them onto flakes of other van der Waals materials or pre-patterned electrodes or waveguides, open unexplored possibilities for magnonics and for the realization of novel YIG-based heterostructures and spintronic devices.